The Freshwater Cyanobacterium Synechococcus elongatus PCC 7942 Does Not Require an Active External Carbonic Anhydrase - Kupriyanova, Elena V.; Sinetova, Maria A.; Gabrielyan, David A.; Los, Dmitry A. (Plants (Basel), 2024)
Under standard laboratory conditions, Synechococcus elongatus PCC 7942 lacks EcaASyn, a periplasmic carbonic anhydrase (CA). In this study, a S. elongatus transformant was created that expressed the homologous EcaACya from Cyanothece sp. ATCC 51142. This additional external CA had no discernible effect on the adaptive responses and physiology of cells exposed to changes similar to those found in S. elongatus natural habitats, such as fluctuating CO2 and HCO3− concentrations and ratios, oxidative or light stress, and high CO2. The transformant had a disadvantage over wild-type cells under certain conditions (Na+ depletion, a reduction in CO2). S. elongatus cells lacked their own EcaASyn in all experimental conditions. The results suggest the presence in S. elongatus of mechanisms that limit the appearance of EcaASyn in the periplasm. For the first time, we offer data on the expression pattern of CCM-associated genes during S. elongatus adaptation to CO2 replacement with HCO3−, as well as cell transfer to high CO2 levels (up to 100%). An increase in CO2 concentration coincides with the suppression of the NDH-14 system, which was previously thought to function constitutively.